2010
DOI: 10.1007/s11250-010-9760-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of raw and roasted soybean in lactating crossbred cows

Abstract: An experiment was conducted to evaluate the effect of roasting whole soybean in the local level on their chemical composition, nitrogen fractions, in situ degradability, and feeding performance in crossbred (Karan Swiss and Karan Fries) dairy cows. Twelve lactating crossbred cattle (369.08 ± 17.53 kg body weight) were randomly divided into two groups on the basis of milk yield (10.18 kg/day) and day of calving (89 days) in a randomized block design. Cows were fed green maize fodder and concentrate mixtures wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…In this study, a no significant different effect on DM intake by dietary RUP supplement was in agreement with some previous studies ( Anderson et al, 2006 ; Sirohi et al, 2011 ). Experimental diets were formulated to be dietary RDP levels at 103.12, 103.27, 97.14, and 100.21 g/kg DM corresponding to the control, R-SBM, DDGS, and SB-DG diets to meet or exceed the nutrient requirements of the lactating cows based on NRC (2001) .…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study, a no significant different effect on DM intake by dietary RUP supplement was in agreement with some previous studies ( Anderson et al, 2006 ; Sirohi et al, 2011 ). Experimental diets were formulated to be dietary RDP levels at 103.12, 103.27, 97.14, and 100.21 g/kg DM corresponding to the control, R-SBM, DDGS, and SB-DG diets to meet or exceed the nutrient requirements of the lactating cows based on NRC (2001) .…”
Section: Discussionsupporting
confidence: 94%
“…It is clear that roasting method should have an appropriate time and temperature combination for effective bypassing rumen. Roasting of soybean led to increase its bypass protein as reflected by increasing in RUP value and a corresponding decrease in effective protein degradability ( Fathi Nasri et al, 2008 ; Sirohi et al, 2011 ). The increase in protein bypass ability was also caused the changes in protein fractions due to heat transfer during roasting ( Fathi Nasri et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Colmenero and Broderick (2006) found that replacing corn grain with soybean meal did not affect DMI, milk production, or diet digestibility when dietary CP level increased from 17.8 to 19.4%, which was similar to the dietary CP range of our study. In addition, Sirohi et al (2011) found that replacing raw soybean with roasted soybean had no effect on performance (DMI and milk production) in lactating crossbred cows. Therefore, DMI and milk production were assumed to be constant, regardless of the combination of CG and SB in the ration.…”
Section: Assumptionsmentioning
confidence: 97%